Pharmacogenomics instruction in US and Canadian medical schools: implications for personalized medicine. (September 2010) - Green, James S; O'Brien, Travis J; Chiappinelli, Vincent A; Harralson, Arthur F
Aims: To determine the extent of pharmacogenomics instruction at US and Canadian medical schools, characterize perceptions of curricular coverage, identify curricular resources and compare responses with similar studies conducted in US pharmacy schools and British medical schools.Materials & methods: A survey was sent to the pharmacology department chairs of US and Canadian medical schools accredited by the Liaison Committee on Medical Education or the American Osteopathic Association's Commission on Osteopathic College Accreditation. Data were collected from July 2009 to February 2010.Results: A total of 56% of eligible medical schools responded (90 out of 160). Of these schools, 82% (74 out of 90) incorporated pharmacogenomics into their curriculum. However, only 28% (21 out of 74) had more than 4 h of the required didactic pharmacogenomic coursework, and only 29% (22 out of 75) were planning to increase the number of pharmacogenomic coursework hours in the next 3 years. Pharmacogenomics coursework was most often contained within a required pharmacology course (66%; 49 out of 74) taught in the second professional year (72%; 53 out of 74). A total of 57% (44 out of 77) considered pharmacogenomics instruction at their own school as 'poor' or 'not at all adequate' while 76% (54 out of 71) considered it 'poor' or 'not at all adequate' at most medical schools.Conclusion: Most US and Canadian medical schools have begun to incorporate pharmacogenomics material into their curriculum; however, the extent of instruction is less than that of US pharmacy schools. To adequately prepare physicians to practice in the era of personalized medicine, medical schools should be encouraged to incorporate greater pharmacogenomic material in their curriculum.